Human Olfactory Bulb Neural Stem Cells (Hu-OBNSCs) Can Be Loaded with Paclitaxel and Used to Inhibit Glioblastoma Cell Growth - Hany E. Marei; Patrizia Casalbore; Asmaa Althani; Valentina Coccè; Carlo Cenciarelli; Giulio Alessandri; Anna T. Brini; Eugenio Parati; Gianpietro Bondiolotti; Augusto Pessina (MDPI AG, 2019)
Exploitation of the potential ability of human olfactory bulb (hOB) cells to carry, release, and deliver an effective, targeted anticancer therapy within the central nervous system (CNS) milieu remains elusive. Previous studies have demonstrated the marked ability of several types of stem cells (such as mesenchymal stem cells (MSCs) to carry and release different anti-cancer agents such as paclitaxel (PTX). Herein we investigate the ability of human olfactory bulb neural stem cells (Hu-OBNSCs) to carry and release paclitaxel, producing effective cytotoxic effects against cancer cells. We isolated Hu-OBNSCs from the hOB, uploaded them with PTX, and studied their potential cytotoxic effects against cancer cells in vitro. Interestingly, the Hu-OBNSCs displayed a five-fold increase in their resistance to the cytotoxicity of PTX, and the PTX-uploaded Hu-OBNSCs were able to inhibit proliferation and invasion, and to trigger marked cytotoxic effects on glioblastoma multiforme (GBM) cancer cells, and Human Caucasian fetal pancreatic adenocarcinoma 1 (CFPAC-1) in vitro. Despite their ability to resist the cytotoxic activity of PTX, the mechanism by which Hu-OBNSCs acquire resistance to PTX is not yet explained. Collectively our data indicate the ability of the Hu-OBNSCs to resist PTX, and to trigger effective cytotoxic effects against GBM cancer cells and CFPAC-1. This indicates their potential to be used as a carrier/vehicle for targeted anti-cancer therapy within the CNS.